Cannabis use is associated with lower odds of prescription opioid analgesic use among HIV-infected individuals with chronic pain - Sohler, Nancy L. (Subst Use Misuse, 2018)
BACKGROUND: Chronic pain is common in the United States and prescribed opioid analgesics use for non-cancer pain has increased dramatically in the past two decades, possibly accounting for the current opioid addiction epidemic. Co-morbid drug use in those prescribed opioid analgesics is common, but there are few data on polysubstance use patterns. OBJECTIVE: We explored patterns of use of cigarette, alcohol, and illicit drugs in HIV-infected people with chronic pain who were prescribed opioid analgesics. METHODS: We conducted a secondary data analysis of screening interviews conducted as part of a parent randomized trial of financial incentives to improve HIV outcomes among drug users. In a convenience sample of people with HIV and chronic pain, we collected self-report data on demographic characteristics; pain; patterns of opioid analgesic use (both prescribed and illicit); cigarette, alcohol, and illicit drug use (including cannabis, heroin, and cocaine) within the past 30 days; and current treatment for drug use and HIV. RESULTS: Almost half of the sample of people with HIV and chronic pain reported current prescribed opioid analgesic use (N=372, 47.1%). Illicit drug use was common (N=505, 63.9%), and cannabis was the most commonly used illicit substance (N=311, 39.4%). In multivariate analyses, only cannabis use was significantly associated with lower odds of prescribed opioid analgesic use (adjusted odds ratio=0.57; 95% confidence interval: 0.38-0.87). CONCLUSIONS/IMPORTANCE: Our data suggest that new medical cannabis legislation might reduce the need for opioid analgesics for pain management, which could help to address adverse events associated with opioid analgesic use.